Stromal cell-based injection therapies for the treatment of knee osteoarthritis: A systematic review of level I randomized controlled trials - Jaydeep Dhillon; James A. Maguire; Matthew J. Kraeutler (Osteoarthritis and Cartilage Open)
Objective: To systematically review randomized controlled trials (RCTs) to compare clinical outcomes of stromal cell-based injection therapies versus other non-operative treatment modalities for the treatment of knee osteoarthritis (OA). Method: A systematic review was performed by searching PubMed, Cochrane Library, and EMBASE to locate RCTs, published since 2019, comparing stromal cell-based injection therapies versus other non-operative modalities for the treatment of knee OA. The search terms used were: knee AND osteoarthritis AND injection AND randomized. Results: Seventeen studies (all Level I evidence) were included in this review with 972 patients undergoing treatment with stromal cell-based therapy (Intervention Group) and 651 patients in the control group (Control Group). Among the 17 studies, 7 used autologous adipose-derived mesenchymal stromal cells (MSCs) (ADMSCs), 2 studies used allogeneic ADMSCs, 4 used autologous bone marrow-derived MSCs (BMMSCs), 1 used allogeneic BMMSCs, 1 used allogeneic placental MSCs, 1 used umbilical cord-derived MSCs (UCMSCs), and 1 study used autologous ADMSCs, BMMSCs, or allogeneic UCMSCs. All but 3 studies reported significantly better clinical or radiological outcomes in the Intervention Group at final follow-up. A total of 5 and 3 studies reported adverse events occurring in the Intervention and the Control groups, respectively, but they were all self-limiting. Conclusions: Patients undergoing treatment of knee OA with MSCs might be expected to experience improvements in clinical and radiological outcomes in comparison to other non-operative modalities. Additional studies with mid-to long-term outcomes are needed to better determine the efficacy and safety of MSCs for the treatment of knee OA.